Optical Enzymatic Biosensor for the Determination of Heavy Metals in the Lagoon of La Paz, Baja California Sur, Mexico - Daniel Santos-Ubaldo; Raúl J. Delgado-Macuil (Proceedings)
An optical crystalline silicon biosensor was developed for the detection of heavy metals in surface water, deep water, mollusks and sediment in the lagoon of La Paz, Baja California Sur, Mexico, to monitor the presence of heavy metals, the biosensor was built using self-assembled monolayers, the silicon supports were cut with a diameter of 0.5 cm × 0.5 cm, chemical modifications were made on the surface by adding KOH to obtain Si-OH groups, for the functionalization this was carried out by 3-aminopropyltrimethoxysilane to add NH2 groups on the surface of the biosensor, the activation was with EDC/NHS as a crosslinking agent, Finally, the urease enzyme was immobilized on the surface of the biosensor in an orbital shaker at 100 rpm in PBS and proceeded to detect each of the concentrations of standard heavy metals methylmercury chloride, cadmium, lead, chromium oxide VI, arsenic oxide III and silver iodide at different concentrations. Subsequently, detection was performed on biological samples by taking the internal part of tissues placed in PBS under refrigeration and water samples were measured without treatment. The self-assembly and detection was characterized by FTIR in the region from 370 to 4000 cm−1 taking the region from 1000 to 1200 cm−1, 1500 to 1700 cm−1 and from 2800 to 3100 cm−1 as the most important regions for the principal component analysis, showing that in these regions the characteristic bonds of silicon are present, The functionalization showed the region of the primary and secondary amide and finally the detection was taken as the inhibition of the enzymatic activity, the principal component analysis showed the region where the detection of each heavy metal is performed and corroborates the results obtained in FTIR.